Multi-level chirality in liquid crystals formed by achiral molecules - Mirosław Salamończyk (Nature Portfolio, 2019)
It was previously shown that chiral structures can be formed from achiral bent-shaped mesogens. Here the authors observe hierarchical chiral structures with coupling of chirality at different levels in a system with achiral constituents.